KARL MARX AND THE KNOWLEDGE OF THE MODERN GLOBAL CRISIS - Nikolaevich Dudin, Mihail; Vladimirovna Levina, Elena; Vladimirovich Churin, Vladimir; Yuryevich Ogorodnikov, Alexander (Revista Inclusiones, 2019)
The subject of the study is the impact of the K. Marx’s theory on the knowledge of the modern global crisis. The purpose of the article is to analyze the Marx’s theories as a source of knowledge of the modern global crisis. Methods. In this work, the authors have used the methods of analysis and synthesis to identify the laws of global economic crisis development, and the comparative historical method to define the stages of the financial crisis development and to compare the characteristics of the crisis in Europe and the United States. The economic and analytical, as well as systemic methods have been used when analyzing and systemizing the empirical data. The obtained materials have been structured and systematized. Results. The article is devoted to studying the impact of the Marx’s theories as a source of knowledge of themodern global crisis. The 2008 –2009 global economic crisis has been considered. The top priority areas of the socio-economic policy of the state to overcome the crisis have been suggested.